STRATEGI PENCEGAHAN, PEMBERANTASAN DAN REHABILITASI PENYALAHGUNA NARKOBA PADA KALANGAN PELAJAR DAN MAHASISWA DI KOTA SEMARANG OLEH BNNP JATENG - Gideon Heru Sukoco; Purwoko .; Muhammad Adnan (Journal of Politic and Government Studies, 2017)
ABSTRACTThis research is motivated by the researchers' concerns about drug abuse among students and students in Semarang City. The high case of narcotics abuse becomes a special attention for the Government which is also very attention to the public in the city of Semarang. Even considering its importance, the Government is calling for an emergency state of narcotics. Therefore, the Government's strategy to overcome drug abuse in accordance with the provisions of Law no. 35 Year 2009 on Narcotics is expected to be able to overcome the problem of Narcotics that occurred.The method used in this research is qualitative research method with descriptive-analysis approach. The purpose of this research is to obtain data on the Government's strategy in overcoming drug abuse among students and college students in the city of Semarang. Assessment and analysis based on interviews and literature studies from reliable sources.The results of this study indicate the strategy of prevention, eradication and rehabilitation of drug abusers among the Students and Students in Semarang City designed by BNNP Central Java is not fully running as expected, so can not reduce the case of drug abuse significantly Based on SWOT analysis it can be known explanation in more detail. And therefore, the Government's role in protecting its citizens from the dangers of drugs should be further enhanced through the optimization of the BNN function, the refinement of the P4GN strategy, and the empowerment of the community, especially for the young generation of the nation's successors, so as to create noble ideals of Indonesia free of narcotics. Keywords:Drug Abuse,P4GN Strategy, Prevention, Eradication, Rehabilitation.